Kapasitas Organisasi Satuan Polisi Pamong Praja Dalam Penyelenggaraan Ketertiban Umum dan Ketenteraman Masyarakat di Kabupaten Bekasi - Mei Anggraeni; Tuswoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The implementation of public order and community peace is one of the mandatory basic services. However, the implementation of public order and public peace in Bekasi Regency found several problems in its implementation which resulted in low organizational capacity. This study aims to describe and evaluate how the Organizational Capacity of the Pamong Praja Police Unit in the implementation of Public Order and Community Order in Bekasi Regency, describe and evaluate what factors hinder the improvement of the Organizational Capacity of the Pamong Praja Police Unit in the implementation of Public Order and Community Order in Bekasi Regency, and describe and evaluate ways or strategies to overcome obstacles to increasing the Organizational Capacity of the Pamong Praja Police Unit in the method used is qualitative. Data collection techniques were carried out by literature study and field research with purposive techniques to select informants. To validate the data, the author used source and technique triangulation techniques. The results showed that the human resources dimension still needs capacity building in terms of training and performance appraisal, especially in terms of discipline. Then from the aspects of infrastructure, technolog, and finance the are still limitations in terms of budget, lack of internal supervision, limited facilities, and minimal availability of technology. Furthermore, in the strategic leadership dimension, there are regulations that are old and not in accordance with the current situation. Then form the aspect of programs and management processes that program planning and formulation are still not optimal because activities still seem to copy form previous years. Furthermore, in Bekasi Regency Pamong Praja Police Unit and cross-sectors and socialization to the community is still minimal.